2009
DOI: 10.1007/s10658-009-9528-x
|View full text |Cite
|
Sign up to set email alerts
|

Seed transmission of Pepino mosaic virus in tomato

Abstract: In Poland in 2002 and 2005 two different isolates of Pepino mosaic virus signed PepMV-SW and PepMV-PK were obtained. Both isolates were compared on the basis of their symptomatology on a series of plant species. In addition, the isolates were characterized by the nucleotide sequence analysis of the triple gene block, coat protein and a part of the polymerase genes. The studies showed that the Polish isolates differ from each other and belong to two strains. PepMV-SW was highly similar to European isolates, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 26 publications
1
40
0
7
Order By: Relevance
“…There is evidence that bumble bees (Shipp et al 2008), the soil-borne fungus Olpidium virulentus (AlfaroFernández et al 2009) and whiteflies (Noël et al 2014) can function as vectors for PepMV. Seed transmission is likely to play a role in long distance spread (Córdoba-Sellés et al 2007;Hanssen et al 2010), and water was confirmed to be the source of PepMV infection (Schwarz et al 2010;Mehle et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that bumble bees (Shipp et al 2008), the soil-borne fungus Olpidium virulentus (AlfaroFernández et al 2009) and whiteflies (Noël et al 2014) can function as vectors for PepMV. Seed transmission is likely to play a role in long distance spread (Córdoba-Sellés et al 2007;Hanssen et al 2010), and water was confirmed to be the source of PepMV infection (Schwarz et al 2010;Mehle et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Entre los mecanismos para la diseminación del virus a larga distancia se encontrarían la transferencia de plántulas afectadas desde los semilleros hasta los agricultores, así como la recientemente demostrada transmisión por semilla (Hanssen et al, 2009a). Así pues, se trata de un tema controvertido, aunque los investigadores sí coinciden en la detección reiteradas veces del virus en la semilla procedente de fruto infectado Ling, 2008;Hanssen et al, 2009a), localizándose éste en la cubierta seminal y resultando dichas partículas virales infectivas tras reinoculación mecánica a Nicotiana benthamiana Domin (Ling, 2008) o a Nicotiana occidentalis H.-H. Wheeler (Hanssen et al, 2009a).…”
Section: Transmisiónunclassified
“…Así pues, se trata de un tema controvertido, aunque los investigadores sí coinciden en la detección reiteradas veces del virus en la semilla procedente de fruto infectado Ling, 2008;Hanssen et al, 2009a), localizándose éste en la cubierta seminal y resultando dichas partículas virales infectivas tras reinoculación mecánica a Nicotiana benthamiana Domin (Ling, 2008) o a Nicotiana occidentalis H.-H. Wheeler (Hanssen et al, 2009a).…”
Section: Transmisiónunclassified
See 1 more Smart Citation
“…Este resultado fue corroborado en un segundo ensayo en el que se observó el hecho de que el porcentaje de transmisión resulta variable con el tiempo transcurrido entre el momento en que la planta madre se infecta con el virus y el momento en que se realiza la recolección de la semilla. Así para periodos de infección de 8 semanas, la tasa de transmisión estimada es del 0.005% mientras que para periodos de 15 semanas, la transmisión aumenta significativamente hasta rondar valores del 0.057% (Hanssen et al, 2009b).…”
Section: DI Is Sc Cu Us Ss Si Io On Nunclassified